Properties of concrete - Neville, Adam M. (Harlow, England : Pearson, 2012)
Properties of Concrete, first published in 1963, has been internationally acclaimed as the definitive work of reference on the subject for both the professional and the student engineer. The fifth edition has been updated to reflect advances in concrete technology over the past decade, yet it still retains the original aim: to provide reliable, comprehensive and practical information on the properties and use of concrete, and the selection of mix proportions all based on scientific observations and the author's extensive engineering experience. The emphasis is on understanding the behaviour of concrete and relating it to physical and chemical phenomena involved in its performance in service, so that the reader to achieve the best possible construction in concrete. Also, the scientific basis of the information provided is invaluable in planning research and in the interpretation of test results.
Includes bibliographical references and indexes.
Buku bacaan asas fakulti
Keywords: Concrete